From supramolecular hydrogels to functional aerogels: a facile strategy to fabricate Fe3O4/N-doped graphene composites1. Issue 94 (14th October 2015) - He, Ting; Li, Zhengyuan; Sun, Zhifang; Chen, Shuzhen; Shen, Rujuan; Yi, Lunzhao; Deng, Liu; Yang, Minghui; Liu, Hongtao; Zhang, Yi
<x xml:space="preserve">Abstract</x> The Fe3O4/N-GAs directly derived from Fc-F/GO supramolecular hydrogels act as multifunctional reagents, including Fe/N sources and the dispersant of GO.